Web of whispers ; Task force PACC ; The other side of Pangasinan [videorecording] - Lazaro, Cheche; Ortigas, Marga; Valdellon, Nessa; Valdez, Luchi Cruz. (Quezon City Probe Productions, 1995)
Probes deeper into the Vizconde case ; examines the PACC and its three years track record ; a tour to Pangasinan.
Web of Whispers (19 min.) -- Task force PACC (13 min.) -- The Other side of Pangasinan (18 min.)
VHS.
Credits : Reporters, Candy Cantada, Cheche Lazaro.
Keywords: Presidential Anti Crime Commission; Vizconde, Massacre of -- 1991. -- Philippines; Industries -- Philippines -- Pangasinan; Massacres -- Philippines; Pangasinan (Philippines) -- Description and travel